FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Purnamasari, Ira (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2015)
This study aimed to determine the effect of asset structure, profitability, company size, growth of sales, liquidity, tax and operation leverage on capital structure. The data in this study using secondary data and the sampling technique in this study using purposive sampling. The criterion are property and real estate company that listing on BEI in 2011-2013, have financial report on rupiah, have no loss and have increasing sales or revenue. There are 31 companies that meet the criterion. Analysis tool used is multiple linear regression. The results showed that asset structure, profitability, company size, growth of sales, liquidity, tax and operation leverage have simultaneously effect on capital structure. Beside that, the results showed that asset structure, profitability, company size, growth of sales, tax and operation leverage have partially effect on capital structure. Unfortunately, liquidity has no partially effect on capital structure.